Preliminary studies on the different roles of T6SSs in pathogenicity of Pseudomonas plecoglossicida NB2011. Issue 11 (25th August 2021) - Jin, Jiamin; Li, Yiying; Huang, Mengxia; Li, Shanshan; Mao, Zhijuan
Abstract: Pseudomonas plecoglossicida, the causative agent of visceral granulomas in the large yellow croaker ( Larimichthys crocea ) in China, encodes three sets of type Ⅵ secretion systems (T6SS1‐3). The purpose of this study was to characterize the different roles of T6SSs involved in infection. In‐frame deletion of T6SSs was constructed, which resulted in 8 mutants. Competition against E. coli DH5α, virulence against the croaker and in vivo survival ability of the mutants were tested. The expression and secretion of Hcp by P. plecoglossicida NB2011 were investigated. The results showed T6SS2 mutant failed to inhibit the growth of E. coli, which is an indication of T6SS2 acting against environmental bacteria. The LD50 value of T6SS1 mutant strongly increased; T6SS2 and T6SS3 mutants were similar to that of the wild type; and the virulence of double deletion or triple deletion mutant was drastically alleviated, indicating that T6SS1 being one of the major virulence factors, and T6SS2 and T6SS3 directly or indirectly being involved in the pathogenicity. T6SS1 mutant disappeared in the fish spleen in 3 days, while other strains kept increasing, indicating the T6SS1 stimulation bacteria replication in vivo. Hcp1 secreted at 12–28°C and Hcp2 secreted at 12–35°C, while Hcp3 secretion not detected in vitro. This study has thrown some insights on the understanding of pathogenicity mechanisms of this pathogen.